1998
DOI: 10.1021/jp972611s
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on the Urea−Hydrogen Peroxide 1:1 Complexes

Abstract: The structures, interaction energies, vibrational analysis, and electronic properties for different urea-hydrogen peroxide (UHP) 1:1 complexes have been studied. Density functional theory (DFT) using the B3LYP hybrid exchange-correlation functional was employed to characterize five new cyclic structures in addition to the experimental one. The basis sets used were Dunning's correlation consistent cc-pVDZ and Pople's 6-31G-(2d,p) ones. Ab initio MP2(full)/6-31G(2d,p)//MP2(full)/6-31G(2d,p) calculations were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 61 publications
(85 reference statements)
4
51
0
Order By: Relevance
“…An additional test was carried out using DFT, which has gained popularity even for treating H-bond interactions [14][15][16][17][18] and thus it has been proposed as a computational method less expensive than MP2 to account for intermolecular electron correlation. It is, however, necessary to carefully evaluate its applicability every time new types of interactions need to be investigated.…”
Section: Validation Of the MM Resultsmentioning
confidence: 99%
“…An additional test was carried out using DFT, which has gained popularity even for treating H-bond interactions [14][15][16][17][18] and thus it has been proposed as a computational method less expensive than MP2 to account for intermolecular electron correlation. It is, however, necessary to carefully evaluate its applicability every time new types of interactions need to be investigated.…”
Section: Validation Of the MM Resultsmentioning
confidence: 99%
“…A major advantage of UHP lies in its potential for releasing anhydrous H 2 O 2 into solution in a controlled manner [51]. Literature survey, revealed that UHP and DABCO-H 2 O 2 are insoluble in common organic solvents such as chloroform as solvent of choice in our reactions [52,53].…”
Section: Introductionmentioning
confidence: 99%
“…4 Theoretical studies of HP complexes have been reported in the literature, including HP dimer, [5][6][7] HP¯water, 8,9 HP¯hydrogen halides, 10 and recently HP¯urea 11 complexes. These studies have been performed mainly by the supermolecule method using the basis set superposition error ͑BSSE͒ correction by the counterpoise method ͑CP͒.…”
Section: Introductionmentioning
confidence: 99%